High yielding mutants from the introgression lines of groundnut (Arachis hypogaea L.): HIGH YIELDING MUTANTS FROM THE INTROGRESSION LINES OF GROUNDNUT - I S TILAK; R S BHAT (Journal of Oilseeds Research, 2021)
An effort was made to generate variability for foliar disease resistance and productivity traits in groundnut using induced mutagenesis with gamma rays and ethyl methane sulfate (EMS) in three interspecific derivatives viz., ICGIL 17105, ICGIL 17110, and ICGIL 17112 involving ABK genomes. A large population of M1, M2, M3 and M4 generations were evaluated along with the parents and checks to identify the promising mutants. Germination percentage decreased with an increase in the dosage of mutagen individually and in combination in the M1 generation. Dominant mutants with reduced plant height were observed along with the lethal mutants in the M1 generation. Gamma rays of 300 Gy and 0.3% EMS showed the highest mutagenic frequency and effectiveness for foliar disease resistance [late leaf spot (LLS) and rust] and productivity traits in the M2 generation. Interestingly, mutations were also observed for the taxonomic traits. Evaluation of M3 lines confirmed the superiority of three mutants over the respective parents and the best check (GPBD 4) for foliar disease resistance and pod yield. Superior mutants were checked for the type of allele at late leafspot (LLS) and rust resistance linked marker loci. Parents and the mutants had the resistant type of allele (like GPBD 4) at all the marker loci (GM1536, GM1954, GM2301, AhTE0498 and AhTE0621). Superior mutants are being evaluated in large plots in the station trial along with the parents and other elite varieties to check their performance towards developing them into commercial varieties.